Amphiphilic Polyphenylene Dendron Conjugates for Surface Remodeling of Adenovirus 5. Issue 14 (3rd February 2020) - Wagner, Jessica; Li, Longjie; Simon, Johanna; Krutzke, Lea; Landfester, Katharina; Mailänder, Volker; Müllen, Klaus; Ng, David Y. W.; Wu, Yuzhou; Weil, Tanja
Abstract: Amphiphilic surface groups play an important role in many biological processes. The synthesis of amphiphilic polyphenylene dendrimer branches (dendrons), providing alternating hydrophilic and lipophilic surface groups and one reactive ethynyl group at the core is reported. The amphiphilic surface groups serve as biorecognition units that bind to the surface of adenovirus 5 (Ad5), which is a common vector in gene therapy. The Ad5/dendron complexes showed high gene transduction efficiencies in coxsackie‐adenovirus receptor (CAR)‐negative cells. Moreover, the dendrons offer incorporation of new functions at the dendron core by in situ post‐modifications, even when bound to the Ad5 surface. Surfaces coated with these dendrons were analyzed for their blood‐protein binding capacity, which is essential to predict their performance in the blood stream. A new platform for introducing bioactive groups to the Ad5 surface without chemically modifying the virus particles is provided. Abstract : Amphiphilic polyphenylene dendrons were prepared and bound to gene vector adenovirus 5 (Ad5) through polar and nonpolar surface groups that control its cellular uptake. The new dendron layer at the Ad5 surface provides reactive groups that are accessible for post‐modifications at the virus surface.